PENGARUH HARGA, KETIDAKPUASAN KONSUMEN DAN KEBUTUHAN MENCARI VARIASI TERHADAP KEPUTUSAN PERPINDAHAN MEREK X KE MEREK Y (Studi Kasus Pada Mahasiswa Fakultas Ekonomika dan Bisnis Universitas Stikubank Semarang) - Eka Pita Sari, 11.05.51.0028 (Students Journal of Economic and Management, 2015)
The purpose of this reseach is to determineÂ  the effect ofprice, dissatisfactionconsumerandrequirement for variation on brand switching decision brand X totransferbrandY. The data used in this research is the primary data, the questionnaire as a research instrument, which is then processed by calculation SPSS (Statistical Product and Solutions) version 19. The population in this study is the Faculty of Economics and Business, University of Stikubank Semarang. The sample used in this study were 100 respondents. The sampling technique in this study using purposive sampling, ie selecting samples according to certain criteria. The analysis tool used is multiple linear regression.The results showed that there is a significant positive effect between the price of the brand switching decision . There is a significant positive effect of consumer dissatisfaction against the decision of brand switching . There is a significant positive effect between the need to find variations on brand switching decision . Keywords: Price , Customer Dissatisfaction , Requirement for variation , and Brand Switching Decision .